A Diguanylate Cyclase Acts as a Cell Division Inhibitor in a Two-Step Response to Reductive and Envelope Stresses - Hyo Kyung Kim (American Society for Microbiology, 2016)
ABSTRACT Cell division arrest is a universal checkpoint in response to environmental assaults that generate cellular stress. In bacteria, the cyclic di-GMP (c-di-GMP) signaling network is one of several signal transduction systems that regulate key processes in response to extra-/intracellular stimuli. Here, we find that the diguanylate cyclase YfiN acts as a bifunctional protein that produces c-di-GMP in response to reductive stress and then dynamically relocates to the division site to arrest cell division in response to envelope stress in Escherichia coli. YfiN localizes to the Z ring by interacting with early division proteins and stalls cell division by preventing the initiation of septal peptidoglycan synthesis. These studies reveal a new role for a diguanylate cyclase in responding to environmental change, as well as a novel mechanism for arresting cell division. IMPORTANCE While the major role of c-di-GMP signaling is to control the decision to move freely or settle in a biofilm, recent studies show a broader range of output functions for c-di-GMP signaling. This work reports an unexpected second role for YfiN, a conserved diguanylate cyclase in Gram-negative bacteria, known to contribute to persistence in the host. We find that YfiN acts as a cell division inhibitor in response to envelope stress. Unlike known cell division inhibitors, the interaction of YfiN with cell division proteins retains the Z ring at the midcell but prevents septal invagination. The new function of YfiN not only emphasizes the versatility of c-di-GMP signaling but describes a novel mechanism for a cell division checkpoint.